An Analysis of the Impact of the Implementation of a Policy Delegating Mineral and Coal Mining Business Permits in North Halmahera Regency - Rifqi, Abdulloh Moh; Darmawan, Arif; Widodo, Joko (Formosa Journal of Multidisciplinary Research, 2024)
This study analyzes the impact of implementing a policy of delegating mineral and coal mining business permits in North Halmahera Regency, aimed at improving the efficiency of the permitting process at the local level. The research focuses on how five key factors in George C. Edward III's Policy Implementation Model communication, resources, disposition of implementers, bureaucratic structure, and external environmental factors influence the success of implementing this policy in the region. The results show that effective communication between the central and local governments is crucial to aligning policy processes. However, disrupted or unstructured communication often leads to miscommunication that hinders policy implementation in the field. This study highlights the need for improvements in communication, strengthening of resources, a more efficient bureaucratic structure, and increased community involvement to achieve the desired goals and fairness in the implementation of mining permit policies. These conclusions provide guidance for policymakers to design a more inclusive and responsive framework for local conditions, enabling sustainable mining in North Halmahera.